Can the State Protect Minority Investors From Tyranny of the Family Shareholders? (A Corporate Governance Comparison Between Indonesia and Korea) - Christiningrum, MF; Aryo Wisnuwardhana, A. (International Journal of Advanced Multidisciplinary, 2024)
In the aftermath of the 1997 Asian Financial Crisis that hit both Indonesia and Korea, both countries’ government saw the needs for revisiting and revitalizing its corporate governance. This case is particularly important given the dominance of family shareholders, both in the form of conglomerates in Indonesia and Chaebol in Korea. This paper aims to analyze the historical trajectory of the corporate governance framework development in both Indonesia and Korea. Based on that research objective, this study finds that despite the fact that both countries were developing the standard according to the latest global norms at the time, the presence of specific business situations and cases in each country forced each country to tailor their corporate governance framework accordingly. These divergent trajectories thus created corporate governance frameworks that are unique for both Indonesia and Korea.